Esperança pela santificação da igreja: uma breve análise sobre a compreensão de "sanrificação" na obra "Pia Desideria" - Brüning, Djonata (Vox Scripturae - Revista Teológica Internacional, 2013)
The current article initially presents an introduction to the biography and the historical context of Philipp Jacob Spener, considered Father of the Protestant Pietism. Following, it presents the central aspects of the comprehension of sanctification found in the work Pia Desideria, pragmatic writing of the Protestant Pietism. The approach points to diverse practical propositions for the personal and communitarian living of a life in sanctification, from which Spener awaited improvements for the situation of the evangelical church of his time.
Keywords: Philipp Jacob Spener; Pietism; Sanctification